Remineralization of enamel subsurface lesions in situ by the use of three commercially available sugar-free gums - DAVID J. MANTON, GLENN D. WALKER, FAN CAI, NATHAN J. COCHRANE, PEIYAN SHEN & (IAPD and Blackwell, 2008)
The beneficial dental effects of chewing sugar-free gum, particularly decreased caries experience, have been reported. The reduction in caries experience is most likely caused by increased salivary flow rates and increased levels of calcium and phosphate in gum-stimulated saliva limiting demineralization and enhancing remineralization.